Prevalence of Pathogens and Antimicrobial Resistance Genes in Lower Respiratory Tract Infections using Multiplex PCR: Insights from a Tertiary Care Hospital in Bangladesh (Bangladesh Critical Care Journal, 2025)
Background: Lower respiratory tract infections (LRTIs) are a major health concern worldwide. The identification of common pathogens and antimicrobial resistance (AMR) patterns is necessary for effective treatment and cost minimization in resource-limited developing countries such as Bangladesh. Objective: This study aimed to detect the prevalence of pathogens and antimicrobial resistance genes in LRTIs using multiplex polymerase chain reaction (PCR) in a tertiary care hospital. Materials & methods: This retrospective observational study analyzed 61 samples, including 46 tracheal aspirates and 15 bronchoalveolar lavage samples, collected between June 2024 and July 2025. The BIOFIRE FILMARRAY pneumonia panel was used to target 27 pathogens, including 9 viruses & 18 bacteria, and 7 antimicrobial resistance (AMR) genes. Data were analyzed using Microsoft Excel-2016. Results: Of the 61 samples, 76.4% tested positive for one or more pathogens. Bacterial pathogens were detected in 64% of the samples, with Klebsiella pneumoniae (34.42%), Pseudomonas aeruginosa (21.31%), and Streptococcus pneumoniae (14.75%) being the most common. Viral pathogens, particularly Human Rhinovirus/Enterovirus (14.74%) and Influenza A (9.83%) were common. Co-infection with both bacteria and viruses was observed in 30% of the samples. AMR genes, particularly CTX-M, an extended spectrum β-lactamase (46.15%), OXA-48-like (38.46%), and NDM (35.89%), both of which are associated with carbapenem resistance, were frequently detected. Conclusion: The high prevalence of multidrug-resistant organisms emphasizes the urgent need for targeted and appropriate antimicrobial therapy for the effective treatment of LRTIs. Continuous surveillance of pathogen prevalence and AMR patterns will help evaluate treatment protocols and local healthcare policies.Bangladesh Crit Care J September 2025; 13 (2): 85-90